2021
DOI: 10.1186/s40462-021-00278-2
|View full text |Cite
|
Sign up to set email alerts
|

GPS tracking reveals landfill closures induce higher foraging effort and habitat switching in gulls

Abstract: Background Landfills are a major subsidy for some animals, with implications for their life history and demography. Gulls feed extensively on food from landfills and closures are expected to have ecological consequences, but how this influences movement ecology is virtually unknown. Methods We used GPS-tracking to quantify foraging behaviour and habitat choice of lesser black-backed gulls (Larus fuscus) breeding at two colonies before and after clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 91 publications
1
26
0
Order By: Relevance
“…We modelled RSFs for the four most visited foraging habitats (agriculture, coastal, marine and urban), fitting separate models for each year. Landfills were previously an important habitat for coastal breeders; however, the closure of a major landfill prior to the study period in April 2017 (Langley et al 2021) meant that this resource was rarely used and was not included in our analysis.…”
Section: Habitat Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…We modelled RSFs for the four most visited foraging habitats (agriculture, coastal, marine and urban), fitting separate models for each year. Landfills were previously an important habitat for coastal breeders; however, the closure of a major landfill prior to the study period in April 2017 (Langley et al 2021) meant that this resource was rarely used and was not included in our analysis.…”
Section: Habitat Selectionmentioning
confidence: 99%
“…However, we note that observed inter-individual differences may partly be driven by variation in the number of fixes and foraging trips. The closure of a large nearby landfill prior to the study period may have influenced the observed patterns of individual habitat use, with birds at the coastal site switching to visiting agricultural habitats more frequently in 2017 postclosure (Langley et al 2021). These findings highlight that while much focus may be on population-level responses, the interindividual differences revealed may be important for management, as problem individuals may have disproportionately large impacts (Sanz-Aguilar et al 2009, Swan et al 2017.…”
Section: Individual-level Habitat Usementioning
confidence: 99%
See 2 more Smart Citations
“…Landscape-independent fragmentation (LIF) results from anthropogenic disturbances which change animals' perception and use of their environment (Berger-Tal & Saltz 2019). For example, resource subsidies lead to LIF whereby fertilized vegetation, gardens, or waste byproducts (Becker et al 2015;Langley et al 2021) provide stable, often predictable, resources which influence wildlife host movement (Ossi et al 2020;Ranc et al 2020) and contact patterns at the human interface, where zoonotic hazard becomes risk. Tick-borne disease emergence is intertwined with land use change and habitat fragmentation (Diuk-Wasser et al 2021) and tick-borne diseases are the most common vector-borne zoonoses in temperate North America, Europe, and Asia.…”
Section: Introductionmentioning
confidence: 99%